A comparison of an educational teaching program on breast feeding effectiveness between individual and group teaching - Lawan Danchai (University of the Philippines Manila, 1985)
This study investigated the problems: 1. Will individualized teaching differ from group teaching in the evaluation of breastfeeding effectiveness? 2. Will program effectiveness of either the individualized teaching or group teaching any relation to: a) age; b) education; c) socioeconomic status; d) occupation; e) duration of postnatal date; f) weight and height of the babies. The following hypotheses were asserted: 1. Structured educational program on breastfeeding given to the primigravidae will increase the knowledge, attitude and technique in breasfeeding practice. 2. There is no difference between individualized and group instruction in increasing the KAP of mothers. 3. There is a relationship between the effectiveness of individualized or group teaching and the following variables : a) age; b) education; c) socioeconomic status; d) occupation; e) duration of postnatal date; f) weight and height of the babies. The subjects were initially assessed on their cognitive level about breastfeeding through the questionnaires for interview and observation checklist. The selection of the sample utilized random assignment. The structured educational program was given to the 2 study groups 4 weeks before their expected date of confinement. The 1st interview was performed on the 2nd day after delivery in the obstetrical ward II by 2 trained observers and the 2nd interview was performed on the 6th week after delivery in well baby clinic by another 2 trained observers. The babies' weight and height were recorded at birth and recorded again at the 6th week after delivery. The data were subjected to the analysis of covariance under SPSS program (Statistical Package for the Social Science). The study resulted on the following findings: 1. Structured educational program on breastfeeding that was given to the primigravidae women increased the knowledge, attitude and technique in breastfeeding practices. 2. The group teaching method was more effective in increasing the KAP of mothers than the individualized teaching method. 3. The relationship between the effectiveness of invidualized or group teaching and the variables age, education, socioeconomic status, occupation, duration of postnatal date, weight and height of the babies.